Position of gender organisations against REDD+ programme in the Cancun 2010 conference - Ahonen, Kirsi (2013)
The aim of this work is to understand what gender organisations participating the Cancun conference in 2010 demanded concerning the planned carbon offset programme, REDD+ , and what kind of alternative approaches they suggested should replace the programme. It was also investigated whom the advocates represented and what were their working methods.